Treatment of primary immune thrombocytopenia in adults: a literature review (Brazilian Journal of Health Research, 2024)
Introduction: Primary Immune Thrombocytopenia is an autoimmune disorder characterized by isolated thrombocytopenia and consequent hemorrhagic phenomen, whitch mechanism is related to platelet destruction by autoantibodies, as well as dysregulation of magakariopoiesis. The clinical presentation is characterized by thrombocytopenia
Keywords: Immune thrombocytopenia; Corticosteroids; Splenectomy; Rituximab